Pengaruh Harga Properti Residensial terhadap Proporsi Kredit Pemilikan Rumah pada Portofolio Kredit di Indonesia - Putera, Matthias Hardy; Kamal, Muhammad Musthafa; Tedjasukmana, Timothy; Chandera, Yane; Saraswati, Dewi (Studi Akuntansi dan Keuangan Indonesia, 2024)
This research aims to analyze the effect of the Residential Property Price Index (RPPI) on the composition of Home Ownership Credit (KPR) in the banking credit portfolio in Indonesia. The study was conducted using secondary data from the period of 2010 to 2022 from various sources such as Bank Indonesia and the Central Bureau of Statistics. Using the time-series regression, the research indicated that RPPI insignificant effected the composition of KPR in the banking credit portfolio in Indonesia. However, inflation rate and interest rates have a significant impact on the proportion of KPR. For credit regulator, this study can add perspectives on the impact of RPPI changes on credit portfolio composition.